2023
DOI: 10.3389/fnins.2023.1188065
|View full text |Cite
|
Sign up to set email alerts
|

Matrix disequilibrium in Alzheimer’s disease and conditions that increase Alzheimer’s disease risk

Abstract: Alzheimer’s Disease (AD) and related dementias are a leading cause of death globally and are predicted to increase in prevalence. Despite this expected increase in the prevalence of AD, we have yet to elucidate the causality of the neurodegeneration observed in AD and we lack effective therapeutics to combat the progressive neuronal loss. Throughout the past 30 years, several non-mutually exclusive hypotheses have arisen to explain the causative pathologies in AD: amyloid cascade, hyper-phosphorylated tau accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 165 publications
(174 reference statements)
0
2
0
Order By: Relevance
“…One limitation of our study, however, is that it is focused on short-term exposure to Tat. Recent studies suggest that while acute inflammation may increase MMPs and reduce ECM accumulation, long term inflammation may instead upregulate ECM deposition in end organs including brain, liver and kidneys (reviewed in Amontree et al, 2023;Ulbrich et al, 2021). We therefore suggest that future studies also examine HIV relevant changes in PNNs in longer-term more indolent models.…”
Section: Discussionmentioning
confidence: 94%
“…One limitation of our study, however, is that it is focused on short-term exposure to Tat. Recent studies suggest that while acute inflammation may increase MMPs and reduce ECM accumulation, long term inflammation may instead upregulate ECM deposition in end organs including brain, liver and kidneys (reviewed in Amontree et al, 2023;Ulbrich et al, 2021). We therefore suggest that future studies also examine HIV relevant changes in PNNs in longer-term more indolent models.…”
Section: Discussionmentioning
confidence: 94%
“…However, its mechanism has not been fully elucidated. In the brain, the progressive nerve injury after an ischemic insult is considered to be mainly due to the neuroinflammatory process, in which the production of dysfunctional cytokines shows up [105], and neurotrophin is considered to play a major role as well [106][107][108]. It has been found that after focal ischemia, Gal3 in microglia is significantly upregulated, which contributes to tissue reconstruction after ischemia [80,105].…”
Section: Retinal Degenerative Diseasementioning
confidence: 99%